2015
DOI: 10.1088/0022-3727/49/4/045303
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Ti thin films by magnetron sputtering at oblique angles

Abstract: The growth of Ti thin films by the magnetron sputtering technique at oblique angles and at room temperature is analysed from both experimental and theoretical points of view. Unlike other materials deposited in similar conditions, the nanostructure development of the Ti layers exhibits an anomalous behaviour when varying both the angle of incidence of the deposition flux and the deposition pressure. At low pressures, a sharp transition from compact to isolated, vertically aligned, nanocolumns is obtained when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 33 publications
8
82
1
Order By: Relevance
“…It was previously shown that the GLAD films morphology is scale-invariant with a power-law scaling connecting thickness and columns' width in xand y-directions [31]. Surface self-diffusion, atomic mobility, ballistic character of incoming particles, or dragging phenomenon are quite a few mechanisms which significantly influence the column broadening and tilting vs. film thickness, and thus, the final structural morphology and anisotropy [32]. Despite several growth simulations in agreement with experimental data and predicting column angle and broadening, the structural anisotropy of GLAD films still remains strongly dependent on operating conditions and experimental methods (cf.…”
Section: Of 18mentioning
confidence: 99%
“…It was previously shown that the GLAD films morphology is scale-invariant with a power-law scaling connecting thickness and columns' width in xand y-directions [31]. Surface self-diffusion, atomic mobility, ballistic character of incoming particles, or dragging phenomenon are quite a few mechanisms which significantly influence the column broadening and tilting vs. film thickness, and thus, the final structural morphology and anisotropy [32]. Despite several growth simulations in agreement with experimental data and predicting column angle and broadening, the structural anisotropy of GLAD films still remains strongly dependent on operating conditions and experimental methods (cf.…”
Section: Of 18mentioning
confidence: 99%
“…Most studies on films produced with obliquely incident vapor flux have concerned metals and oxides [4], which were primarily synthesized at low temperature and low deposited energy (typically by thermal and electron beam evaporation) to benefit from exacerbated shadowing effects [6]. Combining oblique angle geometries and sputter-deposition technique provides additional degree of freedom to adjust the film morphological features (porosity and column tilt angle) and stoichiometry by varying the deposition pressure or target power [7][8][9][10][11] and employing more than one material source [12][13][14][15]. However, studies on transition metal nitride (TMN) films produced at OAD or GLAD conditions remain relatively underexplored [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of gold surface is the most significant feature that influences its functional properties. Gold nanostructures are often prepared by methods of electrochemical deposition [1] but there are a few reports on sputtered micro-/nano-structures [2]- [4]. ZnO doped by Al (ZnO:Al) belongs to transparent conductive oxide (TCO) thin films with specific electronic/optical properties which are applicable in solar cells, optoelectronics and sensorics.…”
Section: Introductionmentioning
confidence: 99%